Polymer-salt interaction - Jun Wei Roy, Chong; Zatul Iffah, Mohd Arshad; Kit Wayne, Chew; Pau Loke, Show (Elsevier, 2023)
Up to this moment, an uprising demand in downstream processing by incorporate innovative, effective, and reliable extraction methods as plenty effort and progression in the upstream production have led to advancement in the biomanufacturing industry. Previously, deployment of conventional downstream technologies has been a hindrance due to high cost, time-consuming, low yield, detrimental, noneco-friendly, lack of simplicity, and difficulties in scaling-up. A new emerging liquid–liquid extraction technology by means the polymer–salt aqueous two phases system for the recovery of biomolecules such as proteins, DNA, and nucleic acids, virus-like particles, and drug residues in food and water. Moreover, the partition coefficient of polyethylene glycol (PEG) 6000-phosphate aqueous two-phase system (ATPS) increased by 62-fold by adding NaCl which results in the recovery of proteins from 90% to 95% in a single purification step. Besides, plasmid DNA successfully recovered by 67% in the PEG-rich phase and managed to partition the contaminants toward the salt-rich phase. The total recovery of 90% from the separation of adenoviral vectors in HEK 293 cells using PEG-ammonium sulfate ATPS. In addition, the recovery of drug residues from food and water corresponds to recovery rate of 96%–100% which is safe for human consumption. This review discusses the following basic mechanism and working principles of ATPS. Factors affecting the partitioning behavior of biomolecules for instance, PEG molecular weight, PEG concentration, system pH, effect of temperature, hydrophobicity, and addition of salt are presented. Future consideration and modification to allow further improvement toward reliable large-scale extraction and purification of biomolecules.